2014
DOI: 10.1007/s00405-014-3385-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated and objective action coding of facial expressions in patients with acute facial palsy

Abstract: Aim of the present observational single center study was to objectively assess facial function in patients with idiopathic facial palsy with a new computer-based system that automatically recognizes action units (AUs) defined by the Facial Action Coding System (FACS). Still photographs using posed facial expressions of 28 healthy subjects and of 299 patients with acute facial palsy were automatically analyzed for bilateral AU expression profiles. All palsies were graded with the House-Brackmann (HB) grading sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
0
11
0
4
Order By: Relevance
“…Kochhar et al revealed an objective reduction of facial asymmetry and improved lip excursions for smiling after hypoglossal-facial jump nerve suture. Recently, we have introduced an automated tool based on a machine learning approach for objective facial action coding and another tool for objective grading of patients with facial palsy (28,29). An important next task will be to apply these objective tools also for evaluation of the patients after hypoglossal-facial jump nerve suture.…”
Section: Discussionmentioning
confidence: 99%
“…Kochhar et al revealed an objective reduction of facial asymmetry and improved lip excursions for smiling after hypoglossal-facial jump nerve suture. Recently, we have introduced an automated tool based on a machine learning approach for objective facial action coding and another tool for objective grading of patients with facial palsy (28,29). An important next task will be to apply these objective tools also for evaluation of the patients after hypoglossal-facial jump nerve suture.…”
Section: Discussionmentioning
confidence: 99%
“…At minimum, and in particular for scientific purpose, photographic documentation or ideally videography should be prerequisite for objective assessment of facial function using automatic image analysis software . The small sample size limited the statistical power of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Der Vorteil dieser Klassifikationssysteme liegt darin, dass diese schnell direkt am Patienten (ungenauer) oder anhand von standardisierten Bildserien erhoben werden können [7]. Neuerdings gibt es auch eine standardisierte Videoinstruktion als Tutorial, welches eine standardisierte Videoaufzeichnung der Fazialisfunktion erlaubt.…”
Section: Subjektive Und Objektive Klassifikation Der Motorischen Faziunclassified